2014
DOI: 10.1182/blood-2013-02-483792
|View full text |Cite
|
Sign up to set email alerts
|

Redefinition of the human mast cell transcriptome by deep-CAGE sequencing

Abstract: Key Points Generated a reference transcriptome for ex vivo, cultured, and stimulated mast cells, contrasted against a broad collection of primary cells. Identified BMPs as function-modulating factors for mast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
230
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(279 citation statements)
references
References 56 publications
(62 reference statements)
25
230
1
Order By: Relevance
“…We recently found that ex vivo and cultured skin MCs strongly differ in their transcriptomes at the whole-genome level (13). Here, we analysed the transition MCs experience on withdrawal from the skin in more detail (i) by extending several data to the protein and functional levels, (ii) by increasing the number of MC donors, (iii) by monitoring the same MC preparations over time and (iv) by investigating cultured MCs not only in the expansion phase but also upon definitive exit from the cell cycle.…”
Section: Questions Addressedmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently found that ex vivo and cultured skin MCs strongly differ in their transcriptomes at the whole-genome level (13). Here, we analysed the transition MCs experience on withdrawal from the skin in more detail (i) by extending several data to the protein and functional levels, (ii) by increasing the number of MC donors, (iii) by monitoring the same MC preparations over time and (iv) by investigating cultured MCs not only in the expansion phase but also upon definitive exit from the cell cycle.…”
Section: Questions Addressedmentioning
confidence: 99%
“…Mast cells were isolated from human breast skin (13)(14)(15) and cultured (in SCF + IL-4) for up to 16 weeks; at defined times, cells were analysed for proliferation (BrdU incorporation), gene expression (quantitative RT-PCR), protein expression (flow cytometry), protease activity, histamine content and stimulation by FceRI-cross-linking. All experimental procedures are detailed in the Supporting Information.…”
Section: Experimental Designmentioning
confidence: 99%
“…Befitting their uniqueness, MCs have no close relative in the hematopoietic network, the best concordance found with hematopoietic progenitor cells. The overall concordance with basophils, the other major effector cell of allergic reactions, is fairly low [5], and the same applies to other myelocytes (SUPPLEMENTARY TABLE 1).…”
Section: The Fantom5 Projectmentioning
confidence: 72%
“…So, what do we really know about these cells in humans? Recent publications by functional annotation of the mammalian genome 5 (FANTOM5), a large consortium dedicated to body-wide transcriptomics and the identification of genomic regions which actually control gene activity revealed that MCs may have properties not associated with the cells before, but conversely lack functions of other immune cells commonly linked to MCs [4,5]. From an allergy point of view, these data not only offer novel insights into how the allergy machinery works at the level of MCs but they also indicate potential novel drug targets for the alleviation of allergy.…”
mentioning
confidence: 99%
“…Based on published microarray databases and RNA sequencing results, we identified the following potential T-cell costimulatory molecules expressed by human mast cells that can be blocked by neutralizing antibodies: OX40L (TNFSF4), ICOSL (B7H2), and LIGHT (TNFSF14) [15,16]. As shown in Figure 5, costimulation by mast cells was not inhibited using blocking antibodies against OX40L, ICOSL, or LIGHT, suggesting that the activation of CD4 + T cells by mast cells was not mediated via these receptor/ligand systems and that other, possibly unknown, receptors are responsible for T-cell costimulation by human mast cells.…”
Section: Cd4 + T-cell Proliferation Induced By MC Does Not Depend Onmentioning
confidence: 99%